Thermocapillary rupture of a horizontal liquid layer on a silicon substrate - Kochkin Dmitry; Belosludtsev Valentin; Sulyaeva Veronica (EPJ Web of Conferences, 2019)
This paper is an experimental study of thermocapillary breakdown phenomenon in a horizontal film of liquid placed on a silicon nonisothermal substrate. With the help of a high-speed video camera the speed of the three-phase contact line was measured during the growth of a dry spot.